1993
DOI: 10.1111/j.1600-0447.1993.tb03368.x
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide survey of seasonal affective disorder at 53 outpatient university clinics in Japan

Abstract: A nationwide survey of seasonal affective disorder (SAD) was performed from autumn 1990 to spring 1991 with the cooperation of 53 outpatient university psychiatric clinics in Japan. Forty-six SAD patients were identified among 5265 depressed outpatients. SAD was generally reported to occur in 1-3% of the depressed outpatients newly attending each facility. Hours of sunshine were found to be a more relevant variable influencing the prevalence of SAD than latitude or the mean temperature in December. The unexpec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
3
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 11 publications
1
24
3
3
Order By: Relevance
“…In a study from Japan (27uN±44uN) (34), total hours of sunshine in winter was found to be a stronger predictor of SAD than latitude. Okawa and fellows (38) have surveyed samples at 6 different latitudes in Japan (31±43uN) with the SPAQ.…”
Section: Speci®c Hypothesesmentioning
confidence: 93%
“…In a study from Japan (27uN±44uN) (34), total hours of sunshine in winter was found to be a stronger predictor of SAD than latitude. Okawa and fellows (38) have surveyed samples at 6 different latitudes in Japan (31±43uN) with the SPAQ.…”
Section: Speci®c Hypothesesmentioning
confidence: 93%
“…The major criterion for the diagnosis o f SA D is its regular occurrence during a certain limited period (60 days) within the course o f a year (see definition), while identical symptoms are not to be found in the same patients in any o f the other months. To date, numerous studies have investigated the phenome nological, epidemiological, and also therapeutic aspects of the clinical picture [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For Japan, a 1995 study by Ozaki et al of 1,276 civil servants showed that a strong association exists in Japan between exposure to sunshine and mood and that, unlike in Western countries, SAD in Japan peaks twice a year: in November (winter) and July (rainy season). Sakamoto et al (1993) show that hours of sunshine have a greater impact on the suicide rate than latitude or temperature. To the best of my knowledge, socioeconomic studies of suicides in Japan so far have not included sunshine, or the interaction of sunshine with economic variables.…”
Section: Socioeconomic Studies Of Suicidementioning
confidence: 97%